A high-order absorbing boundary condition for 2D time-harmonic elastodynamic scattering problems. (15th March 2019) - Mattesi, V.; Darbas, M.; Geuzaine, C.
Abstract: In this paper, we are concerned with the construction of a new high-order Absorbing Boundary Condition (ABC) for 2D-elastic scattering problems. It is defined by an approximate local Dirichlet-to-Neumann (DtN) map. First, we explain the derivation of this approximation. Next, a detailed analytical study in terms of Hankel functions in the circular case is addressed. The new ABC is compared with the standard low-order Lysmer–Kuhlemeyer ABC. Finally, its accuracy and efficiency are investigated for various numerical examples, particularly at high frequencies.